RENEB intercomparison exercises analyzing micronuclei (Cytokinesis-block Micronucleus Assay). (2nd January 2017) - Depuydt, Julie; Baeyens, Ans; Barnard, Stephen; Beinke, Christina; Benedek, Anett; Beukes, Philip; Buraczewska, Iwona; Darroudi, Firouz; De Sanctis, Stefania; Dominguez, Inmaculada; Monteiro Gil, Octávia; Hadjidekova, Valeria; et al.
Abstract: Purpose: In the framework of the 'Realizing the European Network of Biodosimetry' (RENEB) project, two intercomparison exercises were conducted to assess the suitability of an optimized version of the cytokinesis-block micronucleus assay, and to evaluate the capacity of a large laboratory network performing biodosimetry for radiation emergency triages. Twelve European institutions participated in the first exercise, and four non-RENEB labs were added in the second one. Materials and methods: Irradiated blood samples were shipped to participating labs, whose task was to culture these samples and provide a blind dose estimate. Micronucleus analysis was performed by automated, semi-automated and manual procedures. Results: The dose estimates provided by network laboratories were in good agreement with true administered doses. The most accurate estimates were reported for low dose points (≤ 0.94 Gy). For higher dose points (≥ 2.7 Gy) a larger variation in estimates was observed, though in the second exercise the number of acceptable estimates increased satisfactorily. Higher accuracy was achieved with the semi-automated method. Conclusion: The results of the two exercises performed by our network demonstrate that the micronucleus assay is a useful tool for large-scale radiation emergencies, and can be successfully implemented within a large network of laboratories.